CD80 Expression on Tumor Cells Alters Tumor Microenvironment and Efficacy of Cancer Immunotherapy by CTLA-4 Blockade - Vackova, Julie; Polakova, Ingrid; Johari, Shweta Dilip; Smahel, Michal (Cancers, 2021)
Cluster of differentiation (CD) 80 is mainly expressed in immune cells but can also be found in several types of cancer cells. This molecule may either activate or inhibit immune reactions. Here, we determined the immunosuppressive role of CD80 in the tumor microenvironment by CRISPR/Cas9-mediated deactivation of the corresponding gene in the mouse oncogenic TC-1 cell line. The tumor cells with deactivated CD80 (TC-1/dCD80-1) were more immunogenic than parental cells and induced tumors that gained sensitivity to cytotoxic T-lymphocyte antigen 4 (CTLA-4) blockade, as compared with the TC-1 cells. In vivo depletion experiments showed that the deactivation of CD80 switched the pro-tumorigenic effect of macrophages observed in TC-1-induced tumors into an anti-tumorigenic effect in TC-1/dCD80-1 tumors and induced the pro-tumorigenic activity of CD4+ cells. Moreover, the frequency of lymphoid and myeloid cells and the CTLA-4 expression by T helper (Th)17 cells were increased in TC-1/dCD80-1- compared with that in the TC-1-induced tumors. CTLA-4 blockade downregulated the frequencies of most immune cell types and upregulated the frequency of M2 macrophages in the TC-1 tumors, while it increased the frequency of lymphoid cells in TC-1/dCD80-1-induced tumors. Furthermore, the anti-CTLA-4 therapy enhanced the frequency of CD8+ T cells as well as CD4+ T cells, especially for a Th1 subset. Regulatory T cells (Treg) formed the most abundant CD4+ T cell subset in untreated tumors. The anti-CTLA-4 treatment downregulated the frequency of Treg cells with limited immunosuppressive potential in the TC-1 tumors, whereas it enriched this type of Treg cells and decreased the Treg cells with high immunosuppressive potential in TC-1/dCD80-1-induced tumors. The immunosuppressive role of tumor-cell-expressed CD80 should be considered in research into biomarkers for the prediction of cancer patients' sensitivity to immune checkpoint inhibitors and for the development of a tumor-cell-specific CD80 blockade.